Notes on the Relics of the Viking Period of the Northmen in Scotland, illustrated by Specimens in the Museum (Proceedings of the Society of Antiquaries of Scotland, 1873)
The author describes several categories of artefact that he believes to be of Scandinavian origin, discusses how and where they were found, and compares them to Scandinavian finds. He lists examples of urns, brooches, weaponry and items from silver hoards such as jewellery and coins. He concludes by mentioning some Scottish items that were found in graves in Scandinavia, as a way to discuss cultural exchange.